Plan de negocios para la creación de una empresa de tejidos de lana pura ubicada en la parroquia de San Miguel, cantón Salcedo, provincia de Cotopaxi - Palomo Iza, Beatriz Taciana (2015)
The study is fowsing on options developed to form the growth and development of the country, by creating a business plan that allows for the production and marketing of wool garments tected, this need arises because in clothing stores there are in Salcedo. There aren´t wood clothes and the fewthat exist are not quality there isn´t variety ,their designs are not unique, the research methodology was used quantitative in getting numerical dates on supply and demand, qualitative was applied though the surveys that consumer needs are determined….